Could Hypertension in Radiographers Associated with Low Ionizing Radiation Exposure? An Evidence-Based Case Report - I. Wijaya, Rita; C Khoe, Levina; Mansyur, Muchtaruddin (Occupational and Environmental Medicine Journal of Indonesia, 2023)
Low-dose ionizing radiation exposure (